The Starting Treatment for Ethanol in Primary care Trials (STEP Trials): Protocol for Three Parallel Multi-Site Stepped Care Effectiveness Studies for Unhealthy Alcohol Use in HIV-Positive Patients. - Edelman, E Jennifer; Maisto, Stephen A; Hansen, Nathan B; Cutter, Christopher J; Dziura, James; Fiellin, Lynn E; O'Connor, Patrick G; Bedimo, Roger; Gibert, Cynthia; Marconi, Vincent C; Rimland, David; Rodriguez-Barradas, Maria C; et al. (Contemporary clinical trials, 2017)
Unhealthy alcohol use is common among HIV-positive patients, yet effective evidence-based treatments are rarely provided in clinical settings providing HIV care. Further, given patient variability in response to initial treatments, stepped care approaches may be beneficial. We describe the rationale, aims and study design for the current StartingTreatment forEthanol inPrimary care Trials (STEP Trials); three parallel randomized controlled effectiveness trials being conducted in five Infectious Disease Clinics. Participants meeting criteria for: 1) at-risk drinking, 2) moderate alcohol use with liver disease (MALD), or 3) alcohol use disorder (AUD) are randomized to integrated stepped care versus treatment as usual. For those with at-risk drinking or MALD, integrated stepped care starts with a one session brief intervention and follow-up 2-week telephone booster. Based on pre-specified nonresponse criteria, participants may be "stepped up" at week 4 to receive four sessions of motivational enhancement therapy (MET) and "stepped up" again at week 12 for addiction physician management (APM) and consideration of alcohol pharmacotherapy. For those with AUD, integrated stepped care begins with APM. Non-responders may be "stepped up" at week 4 to receive MET and again at week 12 for a higher level of care (e.g. intensive outpatient program). The primary outcome is alcohol consumption assessed at 24weeks, and secondary outcome is the VACS Index, a validated measure of HIV morbidity and mortality risk. Results from the STEP Trials should inform future research and the implementation of interventions to address unhealthy alcohol use among HIV-positive individuals.